Horizontal product differentiation with limited attentive consumers - Marc P. Saur; Markus G. Schlatterer; Stefanie Yvonne Schmitt (Bamberg University, Bamberg Economic Research Group (BERG), 2019)
We analyze the effects of consumers' limited attention on welfare in a model of horizontal product differentiation. We present a novel approach of modeling limited attention: an attention radius. Each consumer only notices goods that are within her attention radius, i.e., goods that are sufficiently similar to her preferred version of the good. Limited attention induces firms to differentiate their products in a way that is beneficial to consumers. In addition, prices may be lower under limited than under full attention. Consumer surplus and welfare are not maximized under full attention but increase for some degree of limited attention.
Keywords: D43; D91; L13; 330; Attention; Horizontal Product Differentiation; Hotelling; Price Discrimination